MACROECONOMIC INDICATORS THAT INFLUENCE ECONOMIC GROWTH IN THE NORTHERN TRIANGLE: A PANEL STUDY, 1990 TO 2021 - Carcamo Sauceda, Lisette Marleny; Paredes Heller, Juan Jacobo; Sorto, José Rodolfo; Salgado, German (LACCEI, 2025)
Economic growth remains one of the main objectives of economic policy [1]. To achieve this, indicators and instruments are developed to promote sustained growth. Monetary, fiscal, and trade policies aim to deliver economic growth results in the short or medium term, ensuring that most of the population benefits from increased income, thereby improving the collective well-being of society. In this regard, the "Solow Model" or Neoclassical Growth Model [2] explains long-term growth based on capital accumulation, population growth, and technological progress [3]. Some authors highlight the crucial role of institutions (both formal and informal) in long-term economic growth, arguing that efficient institutions that protect property rights are essential to encourage investment and innovation [4]. Other authors [5] argue that the Central American region also shares this aspiration and has implemented various economic models in pursuit of growth. However, we ask ourselves: Which indicators contribute to economic growth? In which direction should policies be aimed to have a positive impact on the economy? These are relevant and necessary questions. This research aims to understand how certain macroeconomic variables influence the economic growth of three Central American countries: Guatemala, Honduras, and El Salvador.